REVITALIZATION OF THE KALI GARANG WATERSHED: FROM FLASH FLOODS TO THE CONSTRUCTION OF THE JATIBARANG DAM, 1990–2015 - Jeta Ramadhani; Muzakki Bashori (SOSIOEDUKASI, 2026)
Towards the end of the 20th century, historical records indicate that Semarang was struck by several massive flood disasters, including those in 1973, 1988, and the most severe in 1990. These recurring flood disasters subsequently raised questions regarding how the government and the community responded to the floods that routinely struck Semarang. This paper is an environmental history study aimed at tracing the mitigation measures implemented following the 1990 flash flood in Semarang City. This research employs the historical method by exploring primary sources in the form of contemporaneous newspapers and documents, as well as secondary sources in the form of relevant literature. The revitalization program was implemented as a disaster mitigation measure in the Kali Garang Watershed, which was the location most severely affected by the 1990 flash flood. This program was carried out gradually, starting from small-scale river normalization at the end of 1990 to the construction of the National Strategic Project of the Jatibarang Dam, which officially began operations in 2015. The revitalization efforts of the Kali Garang Watershed area were not an easy task, considering that the broad scope of the watershed became a challenge for all related elements, ranging from stakeholders to the community dealing directly with the ferocity of the Kali Garang. Integrated watershed management serves as a crucial key to breaking the cycle of flood disasters in Semarang City, particularly in the Kali Garang Watershed.